Mimetic Self-Reflexivity and Intersubjectivity in Complementary and Alternative Medicine Practices: The Mirror Neuron System in Breast Cancer Survivorship - Agarwal, Vinita (Frontiers in Integrative Neuroscience, 2021)
This study examines complementary and alternative medicine (CAM) providers’ practices in the treatment of their breast cancer survivor (BCS) clients and interprets these practices within the context of existing neuroscientific research on the mirror neuron system (MNS). Purposive and snowball sampling was conducted to recruit CAM providers (N=15) treating BCSs from integrative medicine centers, educational institutions, private practices, and professional medical associations across the U.S. In-depth semi-structured interviewing (N=252 single-spaced pages) and inductive qualitative content analysis reveal CAM therapeutic practices emphasize a diachronic form of mimetic self-reflexivity and a serendipitous form of mimetic intersubjectivity in BCS pain management to allow the providers to tune-in to their clients’ internal states over time and experience themselves as an embodied subject in an imaginative, shared space. By employing imagination and an intentional vulnerability in their embodied simulation of the others’ internal states, CAM providers co-create experiences of pain while recognizing what about the other remains an unknown. Although MNs provide the mechanism for imitation and simulation underlying empathy through a neuronally wired grasp of the other’s intentionality, the study suggests that examining mimetic self-reflexivity and intersubjectivity in the therapeutic space may allow for a shared simulation of participants’ subjective experiences of pain and potentially inform research on self-recognition and self-other discrimination as an index of self-awareness which implicates the MNS in embodied social cognition in imaginative ways.